ACUTE TOXICITY TEST OF RAMBUTAN HONEY ADHESIVE CREAM AGAINST SWISS WEBSTER MICE (UJI TOKSISITAS AKUT KRIM PEREKAT MADU RAMBUTAN TERHADAP MENCIT SWISS WEBSTER) - Euis Reni Yuslianti; Florence Meliawaty; Afifah B. Sutjiatmo; Ariana Pradita (Fakultas Kedokteran Gigi Unjani, 2022)
Denture adhesive is indicated for conditions of poor retention and stabilization. Commercially available denture adhesives have side effects, thus requiring a safer alternative adhesive, one of which is rambutan honey adhesive cream. Rambutan honey is safe and does not cause toxic effects on test animals. This study aimed to observe the impact of acute toxicity of the orally administered rambutan honey adhesive cream on mice. The research method is an experimental laboratory method and was carried out using 24 male and female Swiss Webster mice. The subject was divided into four groups, one being the negative control group. Rambutan honey adhesive cream was given in three dose groups, namely 1250, 2500, and 5000mg/kg BW. Observations made were death, body weight, behavioural changes, and relative organ weight in mice for fourteen days. The analysis test was carried out using the one-way ANOVA (p < 0.05). The results showed that rambutan honey adhesive cream did not cause death and toxicity symptoms in mice. There was no significant increase in body weight in male and female mice in the group. In the control group, the macroscopic necropsy analysis did not show any change in color and organ index of the heart, lung, liver, spleen, and kidney. This study concludes that the oral administration of rambutan honey adhesive cream on male and female Swiss webster mice is safe and is classified as practically non-toxic. DOI : 10.54052/jhds.sd22.p133-144